Rationalising the First Crusade (1095–1099): Rupert of Deutz, the Roman Conquest of Jerusalem, and the Twists of Salvation History - Alexander Marx (Religions)
Many contemporaries considered the crusader conquest of Jerusalem in 1099 as a significant moment in Salvation History. This article investigates how the reception of the Roman conquest of the city (70 CE) contributed to such an understanding. The important Benedictine exegete Rupert of Deutz (c. 1070–1129) refers to the Roman conquest in 79 passages within his opus, notably in his various biblical commentaries. This case study shows how the past event provided a rationale, exegetical and providential in nature, to understand three dimensions: (a) the role of the Jews, especially that it had been necessary to deprive them of the Holy Land; (b) the current situation of and purpose of Christians in the Holy Land; and (c) the End of Time, which was expected in Jerusalem, and which Rupert anchored already significantly in his own present. His commentary on John’s Revelation even asserted that the Roman conquest had opened the sixth of seven seals (Rev. 6:12). Therefore, the Apocalypse had been ongoing since 70 CE—but only in the Holy Land, a fact that made it necessary for Christians to travel there. The article thus demonstrates that biblical commentaries are potent sources for both crusade studies and historical research in general.